The Influence of Organizational Culture and Workplace Happiness on Organizational Commitment of Civil Servants at the Gang Sehat Community Health Center in Pontianak City - Ahmad Fallah Rifqi; Eru Ahmadia (SAINTIS Publishing, 2025)
This study aims to analyze the influence of organizational culture and workplace happiness on the organizational commitment of civil servants at the Gang Sehat Community Health Center in Pontianak. The approach used is quantitative with an associative research design and saturated sampling technique, involving 38 respondents. Data were collected through interviews with the Head of Administration and questionnaires distributed to all civil servants at the UPT Puskesmas Gang Sehat. Data analysis was conducted using multiple linear regression, multiple correlation coefficient (R), coefficient of determination (R²), simultaneous test (F), and partial test (t). The results of the analysis indicate that both independent variables, organizational culture and workplace happiness, have an influence on organizational commitment. Overall, the results of the multiple linear regression test showed a coefficient of determination (R²) of 0.341, meaning that 34.1% of the variability in organizational commitment can be explained by organizational culture and workplace happiness, while 65.9% is influenced by other factors not examined in this study. Partially, organizational culture was proven to have a significant influence on organizational commitment, while workplace happiness did not have a significant influence. This study suggests that organizations should focus more on developing an organizational culture that supports employee satisfaction, which in turn can increase their commitment and performance. Recommendations for further research: Further research is expected to examine other factors influencing organizational commitment, such as leadership, work motivation, or the physical work environment. Additionally, the study could expand the sample by involving more institutions or sectors to gain broader insights into the influence of organizational culture and workplace happiness on employee commitment under various conditions.